2018
DOI: 10.1177/2472555218773045
|View full text |Cite
|
Sign up to set email alerts
|

Application of Integrated Drug Screening/Kinome Analysis to Identify Inhibitors of Gemcitabine-Resistant Pancreatic Cancer Cell Growth

Abstract: Continuous exposure of a pancreatic cancer cell line MIA PaCa-2 (Mia) to gemcitabine resulted in the formation of a gemcitabine-resistant subline (Mia). In an effort to discover kinase inhibitors that inhibited Mia growth, Mia cells were exposed to kinase inhibitors (PKIS-1 library) in a 384-well screening format. Three compounds (UNC10112721A, UNC10112652A, and UNC10112793A) were identified that inhibited the growth of Mia cells by more than 50% (at 50 nM). Two compounds (UNC10112721A and UNC10112652A) were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 42 publications
3
9
0
Order By: Relevance
“…S2A). This assay is based on kinase inhibitor competition assays to assess kinome-wide inhibitor specificity, similar to that described previously (35, 37).…”
Section: Resultsmentioning
confidence: 99%
“…S2A). This assay is based on kinase inhibitor competition assays to assess kinome-wide inhibitor specificity, similar to that described previously (35, 37).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, at many centers, it is currently only recommended to healthier, younger patients, which may exclude as many as 75% of metastatic PDAC patients (12). While many drug uptake and metabolic mechanisms for resistance to 5-FU and GEM are known (13,14), there is much less understanding of the signaling pathway changes, especially in the global set of protein kinases (i.e., the "kinome") that mediate cell response and survival after treatment with these widely used chemotherapy regimens in PDAC (13,15). Here, we describe an unbiased approach to assessing potential kinase targets for inhibition in combination with FOLFOX.…”
Section: Introductionmentioning
confidence: 99%
“…A study reported by Kant et al (2016) used HTS to identify natural products with antihepatocarcinogenic effects. Krulikas et al (2017) have used HTS to screen kinase targets in gemcitabine-resistant pancreatic cancer cells.…”
Section: Techniques Used To Analyze Gene and Protein Expressionmentioning
confidence: 99%